If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4y + 5 = 0 Reorder the terms: 5 + 2x + -4y = 0 Solving 5 + 2x + -4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 2x + -5 + -4y = 0 + -5 Reorder the terms: 5 + -5 + 2x + -4y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x + -4y = 0 + -5 2x + -4y = 0 + -5 Combine like terms: 0 + -5 = -5 2x + -4y = -5 Add '4y' to each side of the equation. 2x + -4y + 4y = -5 + 4y Combine like terms: -4y + 4y = 0 2x + 0 = -5 + 4y 2x = -5 + 4y Divide each side by '2'. x = -2.5 + 2y Simplifying x = -2.5 + 2y
| -4.1v-1.7=-6.1v+2.3 | | 8z+6=7-14 | | x^2+3x+3= | | 4/3x^2+20/3+25/3=0 | | 3[m+55]=2m+10 | | -6-2=(3x+1)(2) | | -x/8=32 | | 6c^2+4c=0 | | 2v-8=-6v | | 4x+2y-2=0 | | ((6y-1)/4)-((2y-5)/2)=1 | | 12=B*6 | | 2/9/n+2/3=6 | | -3z-6=-3(z+2) | | 12=B*C | | 27x^2=3 | | 2x-21=21-5x | | -35x+52=-53 | | 3(x-4)+1=4(x+1) | | 32-4n+6n-15=79 | | 2(-3v-10)=-6v+21 | | -5/2-2/3 | | 5(6x-1)+7(4x+4)=52 | | (4+x)(4-x)=0 | | 45c^6+54c^8= | | 4u+12=6u | | 3/5+2n=4 | | 3(2n-4)=-9 | | -5y+15=-8y+12 | | 7-8(n+8)=-6(-2n+1)-6 | | 2wn+6=72 | | x^2=1-3x |